Treatment of patients with malignant lymphoproliferative diseases in the Russian Federation: analysis of the data from 75 regions - G. R. Hachatryan; T. S. Teptsova; V. A. Lemeshko; N. Z. Musina (IRBIS LLC, 2019)
The aim is to analyze the medical records of patients with malignant lymphoproliferative diseases (LPD) in the Russian Federation in 2016- 2017. Materials and methods. Treating physicians in 75 regions of the Russian Federation were asked to fill the survey questionnaire containing 9 types of malignant LPDs (according to the ICD-10 classification). The questions covered the epidemiology of LPD (prevalence, resistant forms, relapses and mortality), the existence of specialized institutions and beds, the costs of medical care in patients with malignant LPD, and the financial support of pharmacotherapy in these patients during their hospital stay. Results. We found that the most common malignant LPD in 2016-2017 was Hodgkin's lymphoma (73.5 and 73.4%, respectively). The prevalence of resistant forms and recurrences of malignant LPD over this period accounted for 6.8% of the total patient population. In 2017, the number of patients who died was 7.5% less than that in 2016. There are 815 and 1,763 specialized institutions of the oncology and hematology profiles that provide medical care to children and adult patients, respectively. Among the malignant LPDs, the highest costs of drug therapy in 2016 pertained to lymphosarcoma, and in 2017 - to Hodgkin's lymphoma. In the system of compulsory health insurance (OMC), the largest spending for both adult and pediatric patients in 2016 and 2017 was accounted for Hodgkin's lymphoma; a similar result was obtained for the cost of therapy based on high-tech medical care. Conclusion. In 2017, the total number of patients with malignant LPD in the Russian Federation increased by 2.65% as compared to 2016, while the proportion of primary LPD decreased by 1.2%. In 2017, the total costs of drug supply in patients with malignant LPD in the RF increased by 55.35% as compared with 2016.